2004
DOI: 10.1116/1.1815304
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and electrical characterization of DNA-wrapped carbon nanotube devices

Abstract: In this article we report on the electrical characteristics of single wall carbon nanotubes (SWCNTs) wrapped with single-stranded deoxyribonucleic acid (ssDNA). We fabricate these devices using a solution-based method whereby SWCNTs are dispersed in aqueous solution using 20-mer ssDNA, and are placed across pairs of Au electrodes using alternating current dielectrophoresis (ACDEP). In addition to current voltage characteristics, we evaluate our devices using scanning electron microscopy and atomic force micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…For instance, CNTs are of interest due to their unique physical and chemical properties (including exceptional mechanical properties, [48] and electrical [49] and thermal conductivity [50] ). The introduction of ssDNA onto SWNTs can enhance CNT dispersion in aqueous media for nanodevice fabrication, [51] and presents new exciting opportunities for the precise patterning of CNT layers, whilst DNA-functionalized polymer microbeads are of great interest in the field of combinatorial chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CNTs are of interest due to their unique physical and chemical properties (including exceptional mechanical properties, [48] and electrical [49] and thermal conductivity [50] ). The introduction of ssDNA onto SWNTs can enhance CNT dispersion in aqueous media for nanodevice fabrication, [51] and presents new exciting opportunities for the precise patterning of CNT layers, whilst DNA-functionalized polymer microbeads are of great interest in the field of combinatorial chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ssDNA around the nanotube, compared to other surfactants, does not appreciably affect the overall electrical characteristics of the devices. 4 However, the resistance is higher than for ballistic conductance for metallic SWCNTs. [5][6][7] While the origin of this higher resistance is speculated to be contact resistance between the nanotube and the electrode contact, we aim to develop a deeper understanding of this.…”
Section: Introductionmentioning
confidence: 99%
“…10 The main advantage of this technique is that one can easily vary the electrode material and introduce surface coatings, such as a selfassembled monolayer of an alkylthiol on Au. 4 We characterize the surface chemical composition of our Pd and Pd/PdO electrodes, determine the PdO thickness, and measure the electrical transport across Pd/SWCNT and Pd/PdO/SWCNT junctions. SWCNTs placed directly on clean Pd electrodes indeed form Ohmic contacts, albeit having high resistance, while transport across oxidized Pd electrodes is completely determined by tunneling.…”
Section: Introductionmentioning
confidence: 99%
“…1 insets). A previous study [18] of SWCNT transistors fabricated using very similar ACDEP conditions showed that roughly 1/5 of the devices exhibited semiconducting characteristics, with the rest metallic. No post-deposition annealing was done.…”
Section: Nanomaterials Assembly and Measurementmentioning
confidence: 99%
“…These nanomaterials were separated and put into suspension, and then directly assembled onto broadband co-planar waveguides (CPWs) using AC dielectrophoresis (ACDEP), [17,18] as illustrated in the insets of Fig. 1.…”
Section: Nanomaterials Assembly and Measurementmentioning
confidence: 99%